Acute exercise modifies titin phosphorylation and increases cardiac myofilament stiffness - Müller, Anna E.; Kreiner, Matthias; Kötter, Sebastian; Lassak, Philipp; Bloch, Wilhelm; Suhr, Frank; Krüger, Martina (Frontiers in Physiology, 2014)
Titin-based myofilament stiffness is largely modulated by phosphorylation of its elastic I-band regions N2-Bus (decreases passive stiffness, PT) and PEVK (increases PT). Here, we tested the hypothesis that acute exercise changes titin phosphorylation and modifies myofilament stiffness. Adult rats were exercised on a treadmill for 15min, untrained animals served as controls. Titin phosphorylation was determined by Western blot analysis using phosphospecific antibodies to Ser4099 and Ser4010 in the N2-Bus region (PKG and PKA-dependent. respectively), and to Ser11878 and Ser 12022 in the PEVK region (PKCα and CaMKIIδ-dependent, respectively). Passive tension was determined by step-wise stretching of isolated skinned cardiomyocytes to sarcomere length ranging from 1.9-2.4µm and showed a significantly increased PT from exercised samples, compared to controls. In cardiac samples titin N2-Bus phosphorylation was significantly decreased by 40% at Ser4099, however, no significant changes were observed at Ser4010. PEVK phosphorylation at Ser11878 was significantly increased, which is probably mediated by the observed exercise-induced increase in PKCα activity. Interestingly, relative phosphorylation of Ser12022 was substantially decreased in the exercised samples. Surprisingly, in skeletal samples from acutely exercised animals we detected a significant decrease in PEVK phosphorylation at Ser11878 and an increase in Ser12022 phosphorylation; however, PKCα activity remained unchanged. In summary, our data show that a single exercise bout of 15 min affects titin domain phosphorylation and titin-based myocyte stiffness with obviously divergent effects in cardiac and skeletal muscle tissues. The observed changes in titin stiffness could play an important role in adapting the passive and active properties of the myocardium and the skeletal muscle to increased physical activity.